Exploring the feasibility and acceptability of integrating screening for gender-based violence into HIV counselling and testing for adolescent girls and young women in Tanzania and South Africa - Manuela Colombini; Fiona Scorgie; Anne Stangl; Sheila Harvey; Lethabo Ramskin; Nomhle Khoza; Emma Mashauri; Deborah Baron; Shelley Lees; Saidi Kapiga; Charlotte Watts; Sinead Delany-Moretlwe; et al. (BMC, 2021)
Abstract Background Gender-based violence (GBV) undermines HIV prevention and treatment cascades, particularly among women who report partner violence. Screening for violence during HIV testing, and prior to offering pre-exposure prophylaxis (PrEP) to HIV uninfected women, provides an opportunity to identify those at heightened HIV risk and greater potential for non-adherence or early discontinuation of PrEP. The paper describes our experience with offering integrated GBV screening and referral as part of HIV counselling and testing. This component was implemented within EMPOWER, a demonstration project offering combination HIV prevention, including daily oral PrEP, to young women in South Africa and Tanzania. Methods Between February 2017 and March 2018, a process evaluation was conducted to explore views, experiences and practices of stakeholders (study participants and study clinical staff) during implementation of the GBV screening component. This article assesses the feasibility and acceptability of the approach from multiple stakeholder perspectives, drawing on counselling session observations (n = 10), in-depth interviews with participants aged 16-24 (n = 39) and clinical staff (n = 13), and notes from debriefings with counsellors. Study process data were also collected (e.g. number of women screened and referred). Following a thematic inductive approach, qualitative data were analysed using qualitative software (NVivo 11). Results Findings show that 31% of young women screened positive for GBV and only 10% requested referrals. Overall, study participants accessing PrEP were amenable to being asked about violence during HIV risk assessment, as this offered the opportunity to find emotional relief and seek help, although a few found this traumatic. In both sites, the sensitive and empathetic approach of the staff helped mitigate distress of GBV disclosure. In general, the delivery of GBV screening in HCT proved to be feasible, provided that the basic principles of confidentiality, staff empathy, and absence of judgment were observed. However, uptake of linkage to further care remained low in both sites. Conclusion Most stakeholders found GBV screening acceptable and feasible. Key principles that should be in place for young women to be asked safely about GBV during HIV counselling and testing included respect for confidentiality, a youth-friendly and non-judgmental environment, and a functioning referral network.